“Evaluación de la temperatura y la concentración de azúcar durante la elaboración de vino utilizando levaduras seleccionadas (saccharomyces cerevisiae r. f. cereviseae)” - Vidaurre Rojas, Pierre (2004)
Our research principal aim is to produce red dry wine using dry active yeast Saccharomyces cerevisiae r.f. cerevisae, cultivated in unfermented juice (must) of grapes called "Borgoña Negra" (Vitis labrusca), which is the only variety of grapes cultivated in the San Martin region, PERU, South America. In our experiment research we used unfermented juice of the mentioned grapes to level of 20ºBrix, 23ºBrix and 26ºBrix of sugar concer:ttration which was obtained adding granulated white sugar. During the fermentation process we checked the "yeast" at different temperature levels of 20º C, 25ºC and environment temperature, also, during 30 days. At the beginning, we evaluated nine treatments, which belonged to "musts" of various soluble solid percentages, in relation with the temperatures we have already mentioned. We have chosen the best treatments by using "surface methodology answers", considering the alcoholic capacity of the "yeasts" as the fundament of our research . We evaluated not only the development of the "yeast", but physical and chemical characteristics during the fermentation process, as well. The best selected treatments were submitted to a test (5 points "Hedonic Scale Method"); then, the registered data was analyzed according to "Friedman's Noparametric Test". We conclude that the best studied treatment was the one from 23ºBrix to 25ºBrix. The "experimental" wine was stored during a 90 days period, in which its physical and chemical characteristics were evaluated every 30 days. We noticed stability and small variations in the physical-chemical analysis (density, pH, total acidity, fixed acidity, alcoholic grade, dry total extract, and reducer sugar) and microbiological analysis. Finally, we did a sensorial analysis using the "Ranking Method'', which consisted in making a comparison between our "experimental wine" and two wines available at the local market. Using this test it was determined that consumers of our town, Tarapoto, PERU, would prefer the "experimental wine" (23ºBrix and 25ºBrix) to the other two.